High‐dose alcohol intoxication differentially modulates cognitive subprocesses involved in response inhibition. (6th August 2014) - Stock, Ann‐Kathrin; Schulz, Tom; Lenhardt, Martin; Blaszkewicz, Meinolf; Beste, Christian
Abstract: Aside from well‐known physiological effects, high‐dose alcohol intoxication (a.k.a. binge drinking) can lead to aversive social and legal consequences because response inhibition is usually compromised under the influence of alcohol. Although the behavioral aspects of this phenomenon were reported on extensively, the underlying neurophysiological mechanisms mediating this disinhibition are unclear. To close this gap, we used both behavioral and neurophysiological measures (event‐related potentials, ERPs) to investigate which subprocesses of response inhibition are altered under the influence of high‐dose alcohol intoxication. Using a within‐subject design, we asked young healthy participants ( n = 27) to complete a GO/NOGO task once sober and once intoxicated (approximately 1.2‰). During intoxication, high‐dose alcohol effects were highest in a condition where the participants could not rely on automated stimulus–response mapping processes during response inhibition. In this context, the NOGO‐P3 (ERP), that likely depends on dopaminergic signaling within mesocorticolimbic pathways and is thought to reflect motor inhibition and/or the evaluation of inhibitory processes, was altered in the intoxicated state. In contrast to this, the N2 component, which largely depends on nigrostriatal dopamine pathways and is thought to reflect inhibition on a pre‐motor level, was not altered. Based on these results, we demonstrate that alcohol‐induced changes of dopaminergic neurotransmission do not exert a global effect on response inhibition. Instead, changes are highly subprocess‐specific and seem to mainly target mesocorticolimbic pathways that contribute to motor inhibition and the evaluation of such.